Pengembangan E-Module Keanekaragaman Hayati Bermuatan Potensi Lokal Sumba Berbasis Inkuiri Terbimbing dengan Pendekatan (JAS) untuk Meningkatkan Literasi Lingkungan Siswa SMA - Remindima, Ferdinand Ndawa Lu; Al-Muhdhar, Mimien Henie Irawati; Suhadi, Suhadi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Teaching materials in the form of electronic learning modules really help students and teachers in understanding a learning flow or process. E-Module is a digital learning media that is arranged systematically so that students can learn independently. This research aims to see differences in use of e-module Biodiversity containing Sumba's local potential based on guided inquiry with the JAS approach to increase students' environmental literacy in high school biology material. This study is a Research and Development (R&D) with the Lee & Owens (2004) model. The research population was all class X students of SMA Negeri 6 Malang for the 2024/2025 academic year. The sample in this study was 33 students for the experimental class and 37 students for the control class. Environmental literacy analysis uses the ANACOVA test with a significance level of 5%. The results of the study showed that in the ANACOVA test a significance value of 0.008, which means it is smaller than Î± 0.05 (Sig < 0.05). This confirms that there are significant differences between the classes that use it e-module and those who do not, so that it has an effect on increasing students' environmental literacy. Thus, it can be concluded that the use of e-module Biodiversity containing Sumba's local potential based on guided inquiry using the JAS approach can influence and increase students' environmental literacy.